Identity, recognition and work in post-Fordist society: a path of indepth critical analysis - Bertell, Lucia (Italian Sociological Review, 2013)
From an approach to questions and theories of identity and recognition and through authors that have dealt with them over the last few decades using different political-philosophical perspectives, I have addressed the concept of recognition by focusing on the issue of work from the starting point of Axel Honneth. Self-realization at work and capitalist paradox are combined in a debate with Fraser’s perspectival dualism, continuing the dialogue between the two scholars on recognition and redistribution.